IMPLEMENTASI PERMENDIKBUD NO. 44 TAHUN 2019 TENTANG PENERIMAAN PESERTA DIDIK BARU MELALUI SISTEM ZONASI TAHUN AJARAN 2020/2021 DI SMA NEGERI 50 JAKARTA - Hannyfah Muthiah Hapsari (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2021)
Permendikbud No.44 of 2019 Implementation Concerning The Acceptance of New Students Through The Zoning System For 2020/2021 Academic Year at SMA Negeri 50 Jakarta. Education is an activity that is reversal in human life. Quality and quality education is a very important need for the people of Indonesia, therefore the government is obliged to make improvements in the education sector. The zoning system emerged as a form of equitable education and towards a just education. The purpose of this research is to find out how the implementation of Permendikbud No. 44 of 2019 concerning the admission of new students through the zoning system, to find out what obstacles occur in the implementation of the admission of new students. This study uses the George C. Edward implementation model with a qualitative approach. Data collection techniques using observation, interviews, and documentation related to research. The results of this study found that the implementation of Permendikbud No. 44 of 2019 on the admission of new students at SMA Negeri 50 Jakarta is good and in accordance with the rules that become the reference, while the problem that occurs is the lack of understanding of the parents of students with the socialization given to the zoning system policy and zoning system policies that prioritize age making parents disappointed with the results of the selection obtained.